Comparison of oral health self-assessment results in pregnant women in rural and urban areas: Study quantitative - Nugraha, Rega Mahesa; Suwargiani, Anne Agustina; Aripin, Dudi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Pregnant women are a group of people who are vulnerable to oral health problems due to physical, biological, and hormonal changes. Geographical and administrative location also affects oral health based on the ease of access to health services, which are divided into rural and urban areas. This study aims to analyze the oral health self-assessment of pregnant women in rural and urban areas. Methods: This study employed a quantitative comparative analytical approach with a cross-sectional data collection design, focusing on pregnant women residing in both rural and urban areas. A self-assessment tool, namely the